2013
DOI: 10.4028/www.scientific.net/msf.765.140
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a Hypereutectic Aluminium Silicon Alloy under the Influence of Intensive Melt Shearing

Abstract: A physical modification method with the application of intensive melt shearing during solidification was used to treat a hypereutectic aluminium silicon alloy. The effect of intensive melt shearing on the microstructure of the alloy was studied. Experimental results showed that intensive melt shearing can significantly refine the primary silicon particles, and treatment temperature plays a very important role in the refinement. The optimum condition for refining primary silicon particles of Al-20wt%Si alloy is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In a study, the hypereutectic aluminium alloy was physically modified with intensive melt shearing while solidifying and the effect on the microstructure was examined. 6 The results revealed that the shearing greatly refined the primary silicon with heat treatment playing a significant role; 660°C was recorded as the optimum temperature for Al-20wt%Si alloy Si particle refinement. A centrifugal in situ process was used to fabricate an Al-Al 2 Cu FGM ring from Al-3%Cu in a study, which reported the following findings: the a-Al particles drifted to the outer periphery of the ring; the presence of Cu in the ring was massive in the inner part; the hardness of the Al 2 Cu FGM ring increased towards the inner region and the specimen hardness increased tremendously after heat treatment.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a study, the hypereutectic aluminium alloy was physically modified with intensive melt shearing while solidifying and the effect on the microstructure was examined. 6 The results revealed that the shearing greatly refined the primary silicon with heat treatment playing a significant role; 660°C was recorded as the optimum temperature for Al-20wt%Si alloy Si particle refinement. A centrifugal in situ process was used to fabricate an Al-Al 2 Cu FGM ring from Al-3%Cu in a study, which reported the following findings: the a-Al particles drifted to the outer periphery of the ring; the presence of Cu in the ring was massive in the inner part; the hardness of the Al 2 Cu FGM ring increased towards the inner region and the specimen hardness increased tremendously after heat treatment.…”
Section: Introductionmentioning
confidence: 94%
“…Consequently, this modification and refinement improved the mechanical properties of the alloy. 6,[18][19][20] The inherent attributes of corrosion and wear resistance, light weight, the thermal and electrical conductivity of aluminium and its alloys and composites are resultant effects of microstructure modifications.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation